Bioremediation of biodiesel and diesel contaminated soil by pseudomonas putida - Anak Emparan, Quin (2015)
As occurs to the diesel fuel, the commercialization of biodiesel and their diesel blends can cause environmental damages due to accidental spillage. Presence of these contaminants containing polyaromatic hydrocarbons (PAHs) in soil is toxic to humans, plants and soil microorganisms due to their recalcitrant and mutagenic or carcinogenic properties. Therefore, this study was conducted to suggest a new technique of treatment to clean up the biodiesel and diesel contaminated soil by Pseudomonas putida. Spill simulations with biodiesel, diesel and their blends in sandy gravel soil were performed according to previous study with some modification. Briefly, 200 mL of Pseudomonas putida was inoculated into soil samples: B5 (5% biodiesel + 95% diesel), B20 (20% biodiesel + 80% diesel), B50 (50% biodiesel + 50% diesel), B100 (100% biodiesel) and D100 (100% diesel). As a control sample, there is no addition of biodiesel and diesel into the sample. All samples were stored in the incubator at 35 ºC throughout the 24 days of treatment. Samples were analyzed for: soil particle size, moisture content, pH, total nitrogen (TN), orthophosphate, sulfate, total organic carbon (TOC), soxhlet extraction of PAHs and enumeration of Pseudomonas putida. The measurement of all testing parameters was carried out at interval of three days starting from Day 0 to Day 24 of bioremediation period. Results showed that the highest removal of total nitrogen (TN), orthophosphate, sulfate, total organic carbon (TOC) and PAHs were observed in the sample B100 with up to 70.43%, 69.47%, 68.08%, 97.66% and 96.28% removal, respectively. The degradation rates of PAHs and survival of Pseudomonas putida were also observed highest in the sample B100 with up to 0.149 mg/kg/day and 60 × 106 cfu/g, respectively. Based on these overall findings, it can be verified that the sample B100 has the higher biodegradability than other samples. According to results, it can conclude that, the capability and effectiveness of Pseudomonas putida as oil-biodegradable agent in soil bioremediation were proved and bioremediation of contaminated samples may be considered as a successful and feasible practice.